2017
DOI: 10.1371/journal.pone.0184734
|View full text |Cite
|
Sign up to set email alerts
|

Newborn skin reflection: Proof of concept for a new approach for predicting gestational age at birth. A cross-sectional study

Abstract: BackgroundCurrent methods to assess the gestational age during prenatal care or at birth are a global challenge. Disadvantages, such as low accessibility, high costs, and imprecision of clinical tests and ultrasonography measurements, may compromise health decisions at birth, based on the gestational age. Newborns’ organs and tissues can indirectly indicate their physical maturity, and we hypothesized that evolutionary changes in their skin, detected using an optoelectronic device meter, may aid in estimating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Moreover, our research group reported that neonatal skin reflectance, adjusted by clinical variables, was related to GA, with higher correlation than skin thickness ( R 2 = 0.828, P < 0.001) [ 42 ]. However, both analyses revealed bio-optical properties of the skin at birth as a target to improve maturity scores of GA prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our research group reported that neonatal skin reflectance, adjusted by clinical variables, was related to GA, with higher correlation than skin thickness ( R 2 = 0.828, P < 0.001) [ 42 ]. However, both analyses revealed bio-optical properties of the skin at birth as a target to improve maturity scores of GA prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in light scattering through the skin are believed to be associated with changes in skin thickness, the concentration of chromophores, and light wavelength [ 14 ]. A novel technology was developed to estimate GA at birth (Test-GA) by analyzing the photobiological properties of the newborn’s skin in combination with clinical variables [ 15 ]. This noninvasive and nonionizing technology features a probe containing light emitters and receivers that is brought in contact with the skin over the sole.…”
Section: Introductionmentioning
confidence: 99%
“…This noninvasive and nonionizing technology features a probe containing light emitters and receivers that is brought in contact with the skin over the sole. A mathematical algorithm provides an estimated GA within seconds, combining the skin reflection with clinical adjusters, such as birth weight and incubator stay [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The device under test is easy to use and every effort is being made to ensure that it has excellent accuracy, be it safe and low cost. The feasibility study provided a mathematical model to predict GA based on the skin reflectance adjusted to clinical variables (R 2 =0.828, p<0.001) 15. However, before the adoption or use of an innovation, an effectiveness trial of intervention is a critical step in the research chain regarding its the social utility when completing the translation from the proof of concept to clinical science 15.…”
Section: Introductionmentioning
confidence: 99%